Phosphorus and calcium utilization and requirements in farm animals [ - Kebreab, E.; Vitti, Dorinha M. S. S. (CABI, 2010)
Mineral nutrition of livestock is an area of significant importance due to its contribution to farm animal economics and health. Focusing on macromineral utilization in farm animals, this book brings together quantitative aspects of phosphorus and calcim metabolism in farm animals.